Java programming interviews exposed - Markham, Noel (John Wiley & Sons, Inc, 2014)
"Wrox programmer to programmer"--Cover.; This book has been designed to give you guidance and preparation for finding your next job as a Java developer. It has been written to help you overcome any sense of fear or worry around Java programming interviews by giving you enough material to practice with so that you can feel confident about any questions you might be asked.